The suitability of surface material used at swimming pool area and the surrounding / Nur Izati Azlan - Azlan, Nur Izati (2014)
This research is an attempt to study the suitability of the surface material used and its function of the surrounding. The idea is to observation about the surfacing material of the site must be taken to support the topic of the research. Observation must be made base on the type of surface material used, the functionality of the pavers and the suitability to the site, and the characteristics of the surface material according to its appearance and function. Other than that, observation on the whole design of the site based on the use of its surfacing material.